1990
DOI: 10.1002/tea.3660270405
|View full text |Cite
|
Sign up to set email alerts
|

A study of student perceptions of physics teacher behavior

Abstract: This study investigates student perceptions of the behavior of physics teachers in relation to some other variables in the classroom situation. The research was carried out as a Dutch option of the Second International Science Study. Data were gathered in 65 classrooms of physics teachers with pupils 15 years old. Some of the teachers (21) used the new PLON curriculum and the others a traditional one. Student perceptions of teacher behavior were measured with a questionnaire based on the interpersonal theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 9 publications
3
53
0
1
Order By: Relevance
“…Generally, effects of Proximity are somewhat stronger than effects of Influence. In a study with Physics teachers and their students, Brekelmans et al (1990) found a clear relationship between Proximity and student motivation for Physics. The higher the perception of Proximity, the higher the motivation of the students.…”
Section: Review Of Research On Interpersonal Behaviour and Student Oumentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, effects of Proximity are somewhat stronger than effects of Influence. In a study with Physics teachers and their students, Brekelmans et al (1990) found a clear relationship between Proximity and student motivation for Physics. The higher the perception of Proximity, the higher the motivation of the students.…”
Section: Review Of Research On Interpersonal Behaviour and Student Oumentioning
confidence: 99%
“…In the study by Brekelmans et al (1990) for example, student perceptions of teacher Influence were related to cognitive outcomes. The higher a teacher was perceived on the Influence dimension, the higher the outcomes of students were on a Physics test.…”
Section: Review Of Research On Interpersonal Behaviour and Student Oumentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, high proximity scores relate positively to affective outcomes (e.g. attitudes) (Brekelmans, Wubbels, & Creton, 1990;Brekelmans, van den Eeden, Terwel, & Wubbels, 1997;den Brok, 2001). …”
Section: The Questionnaire On Teacher Interactionmentioning
confidence: 99%